1991
DOI: 10.1192/bjp.159.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Bipolar Disorder on Long-Term Treatment with Lithium

Abstract: The long-term treatment outcome of 248 bipolar patients in an out-patient lithium programme was assessed. Over half of the patients (138 or 56%) had no affective episodes in the year observed. Patients were divided into outcome groups according to GAS scores: the outcome for 40% of patients was good, for 41% fair, and for 19% poor. More frequent psychiatric admissions before starting lithium treatment was the best predictor of poor outcome, followed by a negative affective style in the family and lower social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
160
0
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(174 citation statements)
references
References 34 publications
12
160
0
2
Order By: Relevance
“…This finding suggests that control (or lack of control) of mania may affect the depressive side of bipolar disorder. Supportive of this finding, others have observed that, during lithium treatment, a greater lifetime number of affective episodes (Gelenberg et al, 1989;Harrow et al, 1990;Gitlin et al, 1995;Tohen et al, 1990) or hospitalizations (O'Connell et al, 1991;Harrow et al, 1990) predicts more affective symptoms (O'Connell et al, 1991) or higher rate of affective relapse (Prien et al, 1974;Gelenberg et al, 1989;Harrow et al, 1990;Keller et al, 1992;Aagaard and Vestergaard, 1990). However, predictors for the prophylaxis of depressive morbidity in controlled maintenance studies have not been previously reported.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This finding suggests that control (or lack of control) of mania may affect the depressive side of bipolar disorder. Supportive of this finding, others have observed that, during lithium treatment, a greater lifetime number of affective episodes (Gelenberg et al, 1989;Harrow et al, 1990;Gitlin et al, 1995;Tohen et al, 1990) or hospitalizations (O'Connell et al, 1991;Harrow et al, 1990) predicts more affective symptoms (O'Connell et al, 1991) or higher rate of affective relapse (Prien et al, 1974;Gelenberg et al, 1989;Harrow et al, 1990;Keller et al, 1992;Aagaard and Vestergaard, 1990). However, predictors for the prophylaxis of depressive morbidity in controlled maintenance studies have not been previously reported.…”
Section: Discussionmentioning
confidence: 87%
“…Double-blind, placebo-controlled studies conducted during the 1970s demonstrated that lithium was more effective than placebo at preventing recurrences of bipolar depression (Prien et al, 1973a;Fieve et al, 1976;Goodwin and Jamison, 1990). A later, naturalistic study revealed that approximately 30% of lithium-treated bipolar patients experienced depressive relapse yearly (O'Connell et al, 1991). Lithium has been found to be more effective in the maintenance treatment of 'classical' rather than 'nonclassical' bipolar disorder (Greil et al, 1998), and less effective in rapid cycling, for which several anticonvulsants appear to be more effective (Dunner and Fieve, 1974;Bauer et al, 1994;Calabrese et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report a positive association between clinical course, measured as number of prior admissions 108,109 or past episodes, 110 and interepisode level of functioning. Others have failed to find such relations.…”
Section: Clinical Course and Outcomementioning
confidence: 99%
“…Clinical predictors account for less than half of the variance, [1][2][3][4][5][6][7][8] and there are evidences suggesting that genetic factors play a substantial role in lithium prophylaxis effectiveness. [9][10][11][12][13][14][15][16][17][18][19][20] A large number of studies reported an association between prophylactic lithium response and a family history of bipolar disorder, 10,[12][13][14]17 although not unequivocally confirmed.…”
Section: Introductionmentioning
confidence: 99%